A human norovirus-like particle vaccine adjuvanted with ISCOM or mLT induces cytokine and antibody responses and protection to the homologous GII.4 human norovirus in a gnotobiotic pig disease model - Souza, Menira (2007)
We inoculated gnotobiotic pigs oraly/intranasally with human norovirus GII.4 HS66 strain virus-like particles (VLP) and immunostimulating complexes (ISCOM) or mutant E. coli LT toxin (mLT, R192G) as mucosal adjuvants, then assessed intestinal and systemic antibody and cytokine responses and homologous protection. Both vaccines induced high rates of seroconversion (100%) and coproconversion (75–100%). The VLP+mLT vaccine induced Th1/Th2 serum cytokines and cytokine secreting cells, whereas the VLP+ISCOM vaccine induced Th2 biased responses with significantly elevated IgM, IgA and IgG antibody-secreting cells in intestine. Nevertheless, both vaccines induced increased protection rates against viral shedding and diarrhea (75–100%) compared to controls; however, only 57% of controls shed virus.